2012
DOI: 10.1590/s0100-40422012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades físicas de filmes biodegradáveis à base de amido de mandioca, álcool polivinílico e montmorilonita

Abstract: Recebido em 15/4/11; aceito em 5/9/11; publicado na web em 26/9/11 PHYSICAL PROPERTIES OF BIODEGRADABLE FILMS BASED ON CASSAVA STARCH, POLYVINYL ALCOHOL AND MONTMORILLONITE. The objective of this work was to manufacture biodegradable films based on cassava starch, polyvinyl alcohol (PVA) and sodium montmorillonite (Na-MMT), using glycerol as a plasticizer. These films were characterized according to their microstructure, optical, mechanical, and barrier properties. The combination of starch-PVA-MMT resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…The MMT powder presented an X-ray diffraction spectrum with several types of crystals; however the most relevant ones were observed for 2 = 7 ∘ and 20 ∘ (Figure 3(a)). Similar results were obtained by Faria et al [32] and Cyras et al [27] who also analyzed MMT samples and verified that the first peak occurred for 2 between 7 ∘ and 8 ∘ . The gelatin spectrum was typical of that protein presenting a predominant peak at 2 = 20 ∘ (Figure 3(b)).…”
Section: X-ray Diffractionsupporting
confidence: 88%
“…The MMT powder presented an X-ray diffraction spectrum with several types of crystals; however the most relevant ones were observed for 2 = 7 ∘ and 20 ∘ (Figure 3(a)). Similar results were obtained by Faria et al [32] and Cyras et al [27] who also analyzed MMT samples and verified that the first peak occurred for 2 between 7 ∘ and 8 ∘ . The gelatin spectrum was typical of that protein presenting a predominant peak at 2 = 20 ∘ (Figure 3(b)).…”
Section: X-ray Diffractionsupporting
confidence: 88%
“…[20] Use of biodegradable materials including polymer blends and composites is being assessed worldwide. [21][22][23][24][25][26][27][28][29][30][31][32][33][34] Table 1 shows a few examples of biodegradable polymers and the advantages and disadvantages commonly associated with their use. Of the biodegradable polymers considered, starch blends are produced in the largest quantities and they are followed by polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), polyhydroxyalkanoates (PHA) and other biodegradable materials as shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…The Cloisite ® 30B and Cloisite ® 10A clays is natural MMT that undergo the organophilization process with quaternary ammonium salts MT2EtOH (methyl, tallow, bis-2-hydroxyethyl, quartenary ammonium) and 2MTBHT (dimethyl, benzyl, hydrogenatedtallow, quartenary ammonium), respectively. For example, Faria et al (2012) observed modifications in mechanical properties of biodegradable films-based on starch and polyvinyl alcohol added with sodium montmorrilonite (Closite ® Na + ).…”
Section: Introductionmentioning
confidence: 99%